STUDI KASUS KERAPATAN JALAN HUTAN DI DUA PERUSAHAAN HUTAN DI JAMBI - Dulsalam Dulsalam (Jurnal Penelitian Hasil Hutan, 1994)
A study on the forest road densities was carried out at two logging companies in Jambi in 1990. The objective is to find out the information of forest road densities realized by the companies. Data on area cut and road constructed during the latest ten years felling blocks (from1980/1981 to 1989/1990) were collected. The results of the investigation reveal that:1. Annually, the length offorest roads built by A and B logging companies rangedfrom 2,000 to 13,000 m with an average of 6,050 m, and from 7,600 to 19,800 m with an average of 12, 733 m, respectively.2. Forest road density of each felling block at A and B logging companies ranged from 2.10 to 20 m/ha with an average of 8.54 m/ha, and from3.45 to 22 m/ha with anaverage of 10.02 m/ha, respectively.3. The level of forest road density average in the two logging companies was still bellow those level based on Segebaden Formula.4. It is suggested that log potential, road construction cost and skidding cost be taken into consideration in constructing forest road.